Comparative research on vapor injection heat pump with a novel flash tank - Jinfei Sun; Jianxiang Guo; Longbin He; Shengjun Hou; Zhengchang Yu (Heliyon, 2023)
Two major problems for the vapor injection heat pump systems with the flash tank are the high discharge temperature and the lack of flash tank design theoretical basis, which would limit its wide application in extreme operating conditions. One possible way to overcome these problems is to effectively control the two-phase injection in the flash tank by optimizing its structure. The use of the proposed novel flash tank in the quasi-two-stage vapor injection cycle represents an economic and controllable solution. This research experimentally analyzes the influences of flash tank structure and volume on the system heating performance under different compressor frequencies and injection pressures at the ambient temperature of −10 °C. The comparative analysis is done finding that the novel flash tank could maximumly improve the system Coefficient of Performance (COPh) by 6.4% in this test, compared with the traditional type A flash tank cycle. In the meanwhile, a bad design of novel flash tank size could represent a loss of COPh improvement between 5.73% and 13.5%. Due to the particular structure, the implementation of the novel flash tank also allows the injection mass flow ratio can keep a linear relationship with the injection pressure. Moreover, the refrigerant liquid can be regularly injected into the compression chamber to control discharge temperature under 100 °C. From all the analysis, guidelines for optimizing the control strategy and the flash tank design are put forward, which can be used to perfect the real thermodynamic model of the flash tank rather than the ideal two-phase separation model.